Compact quadruplet bandpass filter based on alternative J/K inverters and λ/4 resonators - Zhang, Songbai (2013)
This letter presents the proposal and synthesis design of a novel compact microstrip quadruplet bandpass filter (BPF) based on alternative J/K inverters and λ/4 resonators. The proposed quadruplet bandpass prototype is firstly derived from the conventional one with lumped LC resonators and the J-inverters. The mainline coupling is implemented by cascading four λ/4 resonators via the alternative J and K inverters, resulting in the achievement of the generalized Chebyshev in-band response. Meanwhile, the first and fourth resonators are cross-coupled via magnetic coupling so as to simultaneously produce transmission zeros below and above the desired passband. Finally, a microstrip quadruplet BPF at 2.5 GHz with a fractional bandwidth of 12.0% is designed, and the measured results of the fabricated filter show consistent match with its theoretical ones.